Safe drinking water status in the state of Bihar, India: challenges ahead - Daya S. Mishra (2009)
Water is a precious resource gifted by nature for the human well being. But its contamination whether chemical or faecal is a challenge for the water supply agencies in providing safe drinking water especially to the rural community. It is a known fact that safe drinking water is essential for healthy living yet millions of people on the earth are deprived of it. Deterioration of ground water quality in recent years due to various human as well as geogenic activities is a threat to humanity especially in rural areas in plains as it is the only available water source within their reach. The governments are struggling to provide adequate safe water to all rural habitations. Depletion of water table in many areas resulting in emergence of chemical impurities like Arsenic and Fluoride in water is making it unsafe whereas water in high water table zone are bacteriologically unsafe. Bihar one of the largest states of Indian Republic with high groundwater potential is facing a serious water quality problem .This paper is a case study and attempts to identify the steps to improve the rural health through safe water supply.